Fluorene‐Based Conjugated Microporous Polymers: Preparation and Chemical Sensing Application. Issue 23 (30th October 2017) - Zhang, Qiujing; Yu, Sen; Wang, Qian; Xiao, Qin; Yue, Yong; Ren, Shijie
Abstract: Conjugated microporous polymers (CMPs) with strong fluorescence are great candidates for optoelectronic applications such as photocatalysis and chemical sensing. A series of novel fluorene‐based conjugated microporous polymers (FCMPs) with different electronic structures are prepared by Yamamoto coupling reactions using rationally designed monomers. The FCMPs show a high degree of microporosity, decent specific surface areas, and variable fluorescence. FCMP3, which possesses a triazine knot in the network, exhibits the highest specific surface area of 489 m 2 g −1, the largest pore volume of 0.30 cm 3 g −1, and the highest solid‐state photoluminescence quantum yield of 11.46%. Chemical sensing performance of FCMPs is studied using a range of nitroaromatic compounds as the analytes. Among the FCMPs, FCMP3 exhibits the highest Stern–Volmer constants of 2541, 4708, and 5241m −1 for the detection of nitrobenzene, 4‐nitrotoluene, 2, 4‐dinitrotoluene, respectively, which are comparable to the detecting efficiency of the state‐of‐the‐art CMP‐based sensing agents. Abstract : Three novel fluorene‐based conjugated microporous polymers (FCMP1–FCMP3) with different electronic structures are prepared by Yamamoto coupling reactions using rationally designed monomers. Among the FCMPs, FCMP3, which possesses the highest specific surface area, largest pore volume, and the highest solid‐state photoluminescence quantum yield, exhibits the largest detecting efficiency for various nitroaromatic compounds.